Review of the Efficacy and Mechanisms of Traditional Chinese Medicines as a Therapeutic Option for Ionizing Radiation Induced Damage - Zhang, Xiaomeng; Chen, Xiaoying; Wang, Lei; He, Changhao; Shi, Zhongyu; Fu, Qian; Xu, Wenhui; Zhang, Shujing; Hu, Sumin (Frontiers in Pharmacology, 2021)
Ionizing radiation damage refers to acute, delayed, or chronic tissue damage associated with ionizing radiation. Specific or effective therapeutic options for systemic injuries induced by ionizing radiation have not been developed. Studies have shown that Chinese herbal Medicine or Chinese Herbal Prescription exhibit preventive properties against radiation damage. These medicines inhibit tissue injuries and promote repair with very minimal side effects. This study reviews traditional Chinese herbal medicines and prescriptions with radiation protective effects as well as their mechanisms of action. The information obtained will guide the development of alternative radioprotectants